Dois fenômenos de apagamento: terminação de formas verbais (3ª p. p. pret. perf. ind.) e -r final de formas nominais - infinitivo - Lameiras, Maria Stela Torres; Mendonça, Helena Alves (Revista Leitura, 2019)
DOI: 10.28998/0103-6858.1995v1n13-14p25-43